The Existence of Symmetric Positive Solutions of Fourth-Order Elastic Beam Equations - Tuz, Munevver (Mdpi, 2019)
In this study, we consider the eigenvalue problems of fourth-order elastic beam equations. By using Avery and Peterson's fixed point theory, we prove the existence of symmetric positive solutions for four-point boundary value problem (BVP). After this, we show that there is at least one positive solution by applying the fixed point theorem of Guo-Krasnosel'skii.
Keywords: four-point boundary value problem; fixed point theorem; symmetric positive solution; cone